Terrorism and Jihad in Islamic Perspective - Doly Andhika Putra; Ni Made Sumaryani (International Journal of Islamic Khazanah, 2021)
Being the most discussed issue in various parts of the world (including Indonesia), Terrorism is considered contrary to humanitarian understanding, which causes losses, both economically, politically, and psychologically. The issue of Terrorism has recently become a hot topic of public discussion. The reason is that terrorists massively use the word Jihad as a justification for their actions. This article uses a descriptive qualitative approach as the primary writing approach. In-depth search for various literature appropriate to the discussion of Jihad and Terrorism from an Islamic point of view. Religion is one of the motivations for a person to join a terror group. Religion is one reason that encourages the emergence of Terrorism due to the oppression that occurs in religion in a specific country. Call it Syria, which is famous for its wars; from there, terrorist groups spread to Indonesia by igniting the spirit of Jihad as citizens who share the same religion share the same fate. After a deeper investigation, the Jihad often campaigned by terror groups is not like Jihad from an Islamic point of view.